Designing A Purifiers Website for Motorcycle Washing and Selling Motorcycle Washing Products - Dimas Sigit Purnomo; Fahmi An Naafi; Fauzan Dwicah Saputra; Fikri Aditya Pratama; Cannes Lingga Yogario (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
In the contemporary era, numerous businesses offer motorcycle washing services and sell motorcycle cleaning products. However, many people still engage in manual transactions, with customers visiting the business premises in person. Purifiers is a business specializing in motorcycle washing services and the sale of motorcycle cleaning products. In conducting its operations, Purifiers facilitates transactions with customers who visit its business location. With the advancements in internet technology, this study aims to create a website to enable online motorcycle washing services and product sales through Purifiers. Customers can initiate transactions through the website, after which Purifiers will visit the customer's location to pick up the motorcycle for washing. Additionally, purchased motorcycle cleaning products will be dispatched either through a courier service or upon the return delivery of the motorcycle to the customer. This research focuses on the design of the Purifiers website for motorcycle washing services and the sale of cleaning products, utilizing the PHP programming language and MySQL database. The methodology employed for the development of this website follows the Software Development Life Cycle (SDLC) with the Waterfall method, encompassing stages such as analysis, design, coding, and testing. Based on the outcomes of the Black Box testing, all menus on the website, both from the admin and user perspectives, function well according to their intended purposes. Furthermore, the results of the Portability testing using various browsers indicate that the website operates smoothly, with all pages displaying correctly.